Crime, migration and social change in North-West England and the Basque country, C.1870-1930 - Winstanley, Michael J.; Blinkhorn, Martin; Pooley, Colin; Tidswell, David (The British journal of criminology, 1999)
This paper offers a comparative analysis of the relationships between crime, policing, urbanization and associated social changes in urban settings in north-west England and the Basque Country of northern Spain, paying special attention to the impact of migration. Two seaside resorts, Blackpool and San Sebastian, and two major seaports, Liverpool and Bilbao, are compared over a period of rapid urban growth during the late nineteenth and early twentieth centuries, and the comparisons are firmly grounded in a broader regional context. Despite the problems involved in comparing across contrasting policing and judicial systems and statistical conventions, it is possible to present profiles of policing, prosecuted crime and attitudes to the law in these English case studies from contrasting attitudes to regional identity and formal and informal approaches to law enforcement